2017
DOI: 10.9775/kvfd.2017.18058
|View full text |Cite
|
Sign up to set email alerts
|

Yumuşak Doku Yaralanması Sonrası Ozon Tedavisinin Etkileri ve IGF-1 Seviyesiyle Olan İlişkisi: Rat Modelinde Deneysel Bir Çalışma

Abstract: Citation of This ArticleÜstebay S, Öztürk Ö, Bilge A, Üstebay DÜ, Tezcan AH: Impacts of ozone treatment and its relationship with IGF-1 levels after injury of soft tissue: An experimental study in rats model. Kafkas Univ Vet Fak Derg, 23 (6): 967-971, 2017. DOI: 10.9775/kvfd.2017 AbstractTo investigate the effects of ozone treatment on soft tissue injury and to observe whether there is an alteration in serum IGF-1 levels after ozone treatment in an experimental rat model. Twenty-four adult Wistar albino 240-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ustebay et al have reported that in an experimental soft tissue injury model in rats, O 3 improved IGF-1 levels. Moreover, the level of IGF-1 was correlated with motor function [49]. No other study evaluated previously the effect of O 3 on any soft tissue injury model and the relation with IGF-1 [49].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ustebay et al have reported that in an experimental soft tissue injury model in rats, O 3 improved IGF-1 levels. Moreover, the level of IGF-1 was correlated with motor function [49]. No other study evaluated previously the effect of O 3 on any soft tissue injury model and the relation with IGF-1 [49].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the level of IGF-1 was correlated with motor function [49]. No other study evaluated previously the effect of O 3 on any soft tissue injury model and the relation with IGF-1 [49].…”
Section: Discussionmentioning
confidence: 91%
“…Ustebay et al have reported that in an experimental soft tissue injury model in rats, O3 improved IGF-1 levels. Moreover, the level of IGF-1 was correlated with motor function 45 . No other study evaluated previously the effect of O3 on any soft tissue injury model and the relation with IGF-1 45 .…”
Section: Discussionmentioning
confidence: 92%
“…(2) Ozone (O 3 ) is widely used for medical purposes as antibacterial, antiviral, antifungal and for healing wounds. (3) The systemic effects of O 3 are the increase of blood flow and oxygen transfer in ischemic tissues, the release of growth factors by the activation of the immune system, the disinfection when topically applied and the stimulation of the neuroendocrine system. It is especially the positive effect on the transportation and release of oxygen to the tissues, the preferred feature for the treatment of different wound types.…”
Section: Efficiency Of Ozone (O 3 ) Therapy On Experimental Acidic Sk...mentioning
confidence: 99%